Nonstandard gravitational waves imply gravitational slip: on the difficulty of partially hiding new gravitational degrees of freedom - Sawicki, Ignacy; Motta, Mariele; Amendola, Luca (Physical review, 2017)
In many generalized models of gravity, perfect fluids in cosmology give rise to gravitational slip. Simultaneously, in very broad classes of such models, the propagation of gravitational waves is altered. We investigate the extent to which there is a one-to-one relationship between these two properties in three classes of models with one extra degree of freedom: scalar (Horndeski and beyond), vector (Einstein-aether), and tensor (bimetric). We prove that in bimetric gravity and Einstein-aether, it is impossible to dynamically hide the gravitational slip on all scales whenever the propagation of gravitational waves is modified. Horndeski models are much more flexible, but it is nonetheless only possible to hide gravitational slip dynamically when the action for perturbations is tuned to evolve in time toward a divergent kinetic term. These results provide an explicit, theoretical argument for the interpretation of future observations if they disfavored the presence of gravitational slip.